Stab wounds: epidemiological profile of emergency room treatment - Robson Cristiano Zandomenighi; Douglas Lima Mouro; Eleine Aparecida Penha Martins (Rev Rene)
The aim of this study was to trace the epidemiological profile from stab wound victims looked after at an emergency department of a university hospital in the year of 2007, characterizing the pre and intra-hospital care. Exploratory studies, transversal, retrospective and descriptive analysis. The sample consisted of 45 victims. Most of the victims were young, from the male sex, single and presented unique injuries caused by interpersonal conflicts. The Integrated Service Attendance to the Trauma at Emergency and the regional transport were the most used ones on the ways to the hospital. The most commonly used procedures at the pre and intra-hospital attendance were respectively: dressing and oxygen therapy; fluid replacement and vesical delay probe. The majority of the victims needed internment, there were little indications of internment to the intensive therapy unit. The injuries did not provoke incapacities, but there were three deaths. Therefore, stab wounds have an epidemiological significance, with the necessity of interventions that will be beyond the health sphere.